PELATIHAN MACROMEDIA FLASH BAGI GURU-GURU JSIT (JARINGAN SEKOLAH ISLAM TERPADU) KAB. SEMARANG SEBAGAI SALAH SATU UPAYA PENINGKATAN INOVASI GURU DALAM PENGAJARAN - Susilawati IKIP PGRI Semarang; Ngurah Ayu N. M.; Siti Patonah; Wijayanto IKIP PGRI Semarang; Didik Aryanto (Universitas PGRI Semarang, 2011)
Abstract Macromedia Flash Training was given to teachers in JSIT Semarang Regency as one of the ways to improve teachers?óÔé¼Ôäó innovation in teaching learning process at school. Besides that, teachers are expected to be able make media which was more interesting in learning process. We used training to guide them in making the learning media.?é?á The result of this program was the increasing the teachers?óÔé¼Ôäó knowledge about the innovation of CRC perspective and teacher?óÔé¼Ôäós creativity in designing media through Macromedia Flash. In other words, the product of its activity was a CD for learning media which was used to teach students successfully. Key words : macromedia flash, learning media, teacher?óÔé¼Ôäós innovation